The Effect of Instagram Advertising Attraction on Purchase Decisions of Tiket.com Online Site Users - Nabela Devinta Puspitaningrum; Mutiatun Himmatul Khoiriyah; Aden Paiq Muntaz; Zulfa Fahmy; Khairani Zikrinawati (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study was to examine the effect of advertising attractiveness on purchasing decisions. This study uses two variables. The independent variable is the attractiveness of advertising on social media (X), and the dependent variable is the purchase decision (Y). The research method this time uses a quantitative method by distributing a Likert scale via Google form to the general public in Indonesia who are using the Tiket.com application. The sample of this research was 100 respondents who were taken randomly (random sampling). The results of this study indicate that advertising attractiveness influences purchase satisfaction at Tiket.com.